Impacts of Government and Household Expenditure on Human Development Index - Sulistyowati, Niken; Sinaga, Bonar Marulitua; Novindra, Novindra (Universitas Negeri Semarang, 2017)
The objective of this reseach are to: (1) analyze the factors affecting human development index and household expenditures for health, education and others, (2) predict the impacts of government expenditure policy in the field of education, health, and infrastructure on human development index in Central Java.Â The model was built using econometric approach in the form of a system of simultaneous equations, including five blocks i.e. government's revenue, expenditures, input, output, and performance. The system of simultaneous equations consisted of 26 equations (19 structural equations and 7 identity equations). The estimation method used Two Stage Least Squares with SYSLIN procedure. Prediction simulation used the stepwise Autoregressive method. The model simulation used Newton's method and SIMNLIN procedure. The results of policy simulation concludes that the combination of the increase in government expenditure for education and infrastructure lead to better performance in increasing income per capita, disposable income and HDI compared to the combination of the policy of the increase in government expenditure for education and in both municipalities and district, but municipalities receive greatest impact compared to the district.